2022
DOI: 10.3390/ijms232012677
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anti-LRRC15 Small Fragments for Imaging Purposes Using a Phage-Display ScFv Approach

Abstract: The human leucine-rich repeat-containing protein 15 (LRRC15) is a membrane protein identified as a marker of CAF (cancer-associated fibroblast) cells whose overexpression is positively correlated with cancer grade and outcome. Nuclear molecular imaging (i.e., SPECT and PET) to track LRRC15 expression could be very useful in guiding further therapeutic strategies. In this study, we developed an ScFv mouse phage-display library to obtain small fragment antibodies against human LRRC15 for molecular imaging purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The application of the phage display approach to create a vaccine against systemic candidiasis was recently proposed in a mouse model [114]. Several experiments have employed phage display to generate antibodies against bacterial toxins such as scFv antibodies against botulinum and alpha-toxin or VHH antibodies against anthrax toxin and Clostridioides Difficile toxin [115]. In a very recent study, Xu et al used phage display to produce a scFv-Fc antibody that neutralized the α-hemolysin toxin of Staphylococcus aureus.…”
Section: Other Diagnostic and Therapeutic Applicationmentioning
confidence: 99%
“…The application of the phage display approach to create a vaccine against systemic candidiasis was recently proposed in a mouse model [114]. Several experiments have employed phage display to generate antibodies against bacterial toxins such as scFv antibodies against botulinum and alpha-toxin or VHH antibodies against anthrax toxin and Clostridioides Difficile toxin [115]. In a very recent study, Xu et al used phage display to produce a scFv-Fc antibody that neutralized the α-hemolysin toxin of Staphylococcus aureus.…”
Section: Other Diagnostic and Therapeutic Applicationmentioning
confidence: 99%
“…They showed that by using the phage display technique, a fast-track development can be provided to obtain antibodies for imaging and diagnostic purposes. 53 In a 2013 study by Tsedev et al, they engineered an M13-derived small filamentous phage called "inho" by constructing a collection of small phage ssDNA packaged by M13 capsid proteins. 54 The 50 nm size of this phage makes it advantageous for use in the diagnosis, imaging and treatment of human tumors.…”
Section: Bacteriophage Application In Identification Of Tumor Markersmentioning
confidence: 99%
“…After biopanning, a suitable single‐chain variable fragment molecule was selected and radiolabeled through bioconjugation. They showed that by using the phage display technique, a fast‐track development can be provided to obtain antibodies for imaging and diagnostic purposes 53 . In a 2013 study by Tsedev et al., they engineered an M13‐derived small filamentous phage called “inho” by constructing a collection of small phage ssDNA packaged by M13 capsid proteins 54 .…”
Section: Bacteriophage Applications In Medical Oncologymentioning
confidence: 99%
“…A chimeric Fab library (the variable part from the rabbit and the constant Fab part from the mouse Kappa/IgG1 domain) was built in our proprietary phagemid [17]. The histidine tag was followed by a Myctag in the C-terminal part of the construction (Scheme 1).…”
Section: Library Constructionmentioning
confidence: 99%
“…The rabbit variable IgG VH and VL sequences were amplified following 2 rounds of successive PCRs using a set of primers adapted from Nguyen et al [18]. The PCR protocol was a modification of the method used by Baurand et al [17]. The first PCR rounds were performed to amplify the VH or VL sequences starting from the cDNA.…”
Section: Library Constructionmentioning
confidence: 99%